Method for Determining the Number of Propellers in an Aircraft from a Radar Image Obtained by Inverse Synthesis of the Antenna Aperture - S. R. Heister; V. V. Kirychenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The inverse antenna aperture synthesis technology used to construct a radar image of an aircraft’s propellers has shown high eﬃciency. The radar image allows to visualize the blades of the rotors included in the functional group (traction rotors of an aircraft, rotors of a twin-rotor helicopter, rotors of a multicopter). In the case of a single rotor in an aircraft (an airplane’s tractor rotor, a single-rotor helicopter’s main rotor), the radar image is simple and clearly perceptible. In the case of several propellers belonging to the same functional group, the ana ysis of the radar image becomes signiﬁcantly more complicated. This is due to the random relative position of the blades of diﬀerent propellers at the moment the image begins to be constructed, as well as the possible random coincidence of the spatial position of the blades belonging to diﬀerent propellers. In this regard, determining the number of propellers in an aircraft is a new urgent task, the solution of which allows us to obtain additional information for recognition. The method under consideration for determining the number of propellers is based on the most common design features – the blades in the propeller follow at the same angular interval, in the propellers of the functional group the number of blades is the same.